Biomechanical analysis of spine movements in hiking on sailing: a preliminary study - Sprada de Menezes, F.; Schütz, G. R.; Cerutti, P. R.; Carneiro, L. C.; Fontana, H. B.; Roesler, H. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
This study aimed to evaluate sailors` vertebral spine movements and positioning during hiking position. One Laser Class sailor composed the sample. Four 60Hz Peak Motus System® cameras were used. To evaluate some spine angles the following points were chosen: in saggital plane - the neck flexion angle, thoracic kiphosis angle and lumbar lordosis angle; in frontal plane - the lateral inclination angle; in transversal plane - the trunk rotation. Data were analysed through descriptive statistics. The analysis shows great angle variations performed in a 10s hiking execution. It can be observed that the sailor`s trunk performs, in the three axes, a sum of movements during the technical gesture. It was demonstrated that hiking is not a static posture and to study this position researchers should not consider trunk as a fixed segment.